2004
DOI: 10.1074/jbc.m312985200
|View full text |Cite
|
Sign up to set email alerts
|

Cell Type-specific Expression of LINE-1 Open Reading Frames 1 and 2 in Fetal and Adult Human Tissues

Abstract: The LINE-1 (L1) family of non-long terminal repeat retrotransposons is a major force shaping mammalian genomes, and its members can alter the genome in many ways. Mutational analyses have shown that coexpression of functional proteins encoded by the two L1-specific open reading frames, ORF1 and ORF2, is an essential prerequisite for the propagation of L1 elements in the genome. However, all efforts to identify ORF2-encoded proteins have failed so far. Here, applying a novel antibody we report the presence of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
176
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(191 citation statements)
references
References 47 publications
(62 reference statements)
12
176
0
1
Order By: Relevance
“…In control (pS-neo) cells, the L1-encoded protein exhibits a discrete localization, close or adjacent to the nuclear envelope (panels a and b); in contrast, no signal is detected in the pS-L1 interfered cells (panels c and d). Western blot analysis ( Figure 2B) revealed the full-length protein (150 kDa) encoded by L1 ORF2, as well as lower molecular weight protein species, as expected (Ergun et al, 2004). Roles of LINE-1 and HERV-K in tumorigenesis E Oricchio et al relative to tubulin signals confirmed a drastic reduction (about 80%) of L1-encoded proteins in interfered (pS-L1i) compared to control (pS-neo) cell extracts ( Figure 2C).…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…In control (pS-neo) cells, the L1-encoded protein exhibits a discrete localization, close or adjacent to the nuclear envelope (panels a and b); in contrast, no signal is detected in the pS-L1 interfered cells (panels c and d). Western blot analysis ( Figure 2B) revealed the full-length protein (150 kDa) encoded by L1 ORF2, as well as lower molecular weight protein species, as expected (Ergun et al, 2004). Roles of LINE-1 and HERV-K in tumorigenesis E Oricchio et al relative to tubulin signals confirmed a drastic reduction (about 80%) of L1-encoded proteins in interfered (pS-L1i) compared to control (pS-neo) cell extracts ( Figure 2C).…”
Section: Resultssupporting
confidence: 66%
“…The effectiveness of interference against L1 expression compared to control cells infected with empty vector (pS-neo) was assessed by immunofluorescence (IF), RT-PCR and immunoblotting analyses. Figure 2A shows an IF assay using an antibody (anti-L1EN), raised against polypeptides encoded by the endonuclease (EN)-domain of L1 ORF2 (Ergun et al, 2004), in A-375 cells infected with either vector alone (pS-neo), or with L1-interfering construct (pS-L1i). In control (pS-neo) cells, the L1-encoded protein exhibits a discrete localization, close or adjacent to the nuclear envelope (panels a and b); in contrast, no signal is detected in the pS-L1 interfered cells (panels c and d).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At 72 h after L1-i transfection, expression of both ORF1 and ORF2 was reduced by almost 80% compared to cells transfected with noninterfering oligonucleotide (Figure 5c). To ascertain that the RT protein product was consistently downregulated in L1-i interfered cells, we made use of a recently developed antibody against LINE-1 ORF2-encoded RT (termed EN-L1, Ergun et al, 2004). Immunoprecipitation and Western blot assays indicate that RT protein levels 72 h after transfection are significantly reduced in L1-i cells (Figure 5d).…”
Section: Rna Interference (Rnai) Against Rt-encoding Line-1 Elements mentioning
confidence: 99%